2022
DOI: 10.3389/fncel.2021.768711
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells From Different Donors on Spinal Cord Injury in Mice

Abstract: Spinal cord injury (SCI) is caused by an external force, leading to severe dysfunction of the limbs below the injured segment. The inflammatory response plays a vital role in the prognosis of SCI. Human umbilical cord mesenchymal stem cell (hUCMSC) transplantation can promote repair of SCI by reducing the inflammatory response. We previously showed that hUCMSCs from 32 donors had different inhibitory abilities on BV2 cell proliferation. In this study, three experimental groups were established, and the mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…The neuroprotective effect of HUC-MSCs on SCI has been widely recognized, especially by inhibiting inflammatory response. 22,23 Levels of TGF-β secreted by the activated immune cells were increased during the inflammatory response. Zhou et al 24 found that IL-10 has a direct nutritional impact on spinal cord neurons: the Il-10 receptor that activates neurons can provide nutritional support for overcoming glutamate neurotoxicity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of HUC-MSCs on SCI has been widely recognized, especially by inhibiting inflammatory response. 22,23 Levels of TGF-β secreted by the activated immune cells were increased during the inflammatory response. Zhou et al 24 found that IL-10 has a direct nutritional impact on spinal cord neurons: the Il-10 receptor that activates neurons can provide nutritional support for overcoming glutamate neurotoxicity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In different subacute SCI mouse models, injection of human UC-MSCs into the center of the injury area decreased the local levels of several proinflammatory cytokines such as TNF-α, IFN-γ, IL-6, and IL-7, in addition to promoting the transition of macrophages to the M2 type, attenuating the local inflammatory response and resulting in tissue repair and motor-function recovery (Bao et al, 2018 ; Wu et al, 2020 ). Differences in the ability to inhibit the inflammatory response between human UC-MSCs from different donors are determinants of their effectiveness in the recovery of mice after SCI (Zhu et al, 2022 ). Intrathecal transplantation of human UC-MSCs in rats with subacute SCI promoted regeneration and remyelination, as well as reduced astrogliosis, decreased cavity and glial scar formation, and supported functional recovery (Yang et al, 2020 ; Cao et al, 2022 ).…”
Section: Msc Therapy In Neurological Diseasesmentioning
confidence: 99%
“…Post-translational tubulin modifications are relevant for axonal regeneration as it regulates cytoskeleton dynamics. A variety of post-translational modifications were described to occur following SCI, such as tyrosination, acetylation, and phosphorylation ( Zhu et al, 2022 ). Axon injury induces a gradient of tubulin deacetylation, reducing stable microtubules in proximity of the injury site, an effect that is necessary for growth cone dynamics and axon regeneration, and specific to peripheral neurons, failing to occur in central neurons.…”
Section: Microtubule Dynamics: the Overlooked Underdog Underlying Axo...mentioning
confidence: 99%
“…α-Tubulin deacetylation in PNS axons is initiated by calcium influx at the site of injury, and requires protein kinase C (PKC)-mediated activation of the histone deacetylase 5 (HDAC5) ( Cho and Cavalli, 2012 ). Such a reduction in microtubule acetylation does not occur in the CNS, suggesting that tubulin modifications that accompany microtubule stability negatively impact the capacity of the axon to regenerate ( Zhu et al, 2022 ). In fact, HDAC5 knockdown and inhibition restricts growth cone dynamics and regeneration of dorsal root ganglion (DRG) neurons both in vitro and in vivo and in CGNs, whereas HDAC5 overexpression had the opposite effect ( Rivieccio et al, 2009 ; Gaub et al, 2010 ; Cho and Cavalli, 2012 ).…”
Section: Microtubule Dynamics: the Overlooked Underdog Underlying Axo...mentioning
confidence: 99%
See 1 more Smart Citation